Applying Existing Reading Research : To Improve English Reading Comprehension in Icelandic Secondary Schools - Constance Lynne Clark 1961- (2015)
The purpose of this thesis was to examine research on collaborative reading models, the learning of strategies for improving reading comprehension for secondary students of English as a second or foreign language (hereafter referred to as the L2), and to provide intervention measures that target struggling readers before remedial recommendations become necessary. The particular focus draws from research of both native-speaking English language (L1) learners and L2 learners. Few studies are available of L2 upper secondary language learners using these models and approaches. However, studies of the essential reading components needed for literacy and reading comprehension among L1 learners may provide useful help for struggling L2 readers to increase their reading comprehension of English academic texts. This thesis is a formative exploratory literature review within the framework of cognitive linguistics, and builds on the research of others. The aim was to inform my own practice and educators in Iceland. This study draws on research from cognitive theories for second language learning. People are social beings, and literacy development begins with collaborative social exchanges amongst humans. Therefore, collaborative language learning and strategy learning may be effective ways for improving reading comprehension for adolescent learners. Furthermore, the study explored the mastering of primary language components necessary for reading in an Alphabetic Writing System, because research indicates that some adolescents struggling with reading comprehension may suffer from insufficient component skills related to reading. These component skill prerequisites are the alphabetic principle and alphabetics, which include the phonological components—phonetics and phonemics, and phonics, in addition to word-level and sentence-level reading fluency. I refer to secondary aspects affecting reading comprehension, which take time to learn, such as background and vocabulary knowledge, strategy instruction, and cognitive ...